THE SIGNIFICANCE OF PHILOSOPHY OF SCIENCE FOR HUMANITY IN ISLAMIC PERSPECTIVE - Zaprulkhan Zaprulkhan (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
In Islamic perspective, researching universe is not only investigate the universe materially but also what is behind the universe itself. So, the universe was not viewed autonomously. This paper tried to elaborate significance of philosophy of science for humanity in Islamic perspective by using three fundamental structures of knowledge, namely ontology, epistemology, and axiology. Both Islam and science have to put humanity as center for research. The paradigm of Islamic science opens up an integral-holistic thought, and can not be separated from axiological meaning, that the purposes toward the enlightenment, progress, welfare, safety, and happiness for the whole human being in this world. So, Islam and science could give the most important roles to human’s welfare and safety.